Traumatic Pancreatic Injury Presentation, Management, and Outcome: An Observational Retrospective Study From a Level 1 Trauma Center - Al-Thani, Hassan; Ramzee, Ahmed Faidh; Al-Hassani, Ammar; Strandvik, Gustav; El-Menyar, Ayman (Frontiers in Surgery, 2022)
Background: We aimed to study the presentation, management, and outcomes of patients with pancreatic traumatic injury. Methods: We retrospectively analyzed data for all patients who were admitted with pancreatic injuries between 2011 and 2017 at the only level 1 trauma center in the country. Results: There were 71 patients admitted with pancreatic trauma (0.6% of trauma admissions and 3.4% of abdominal injury admissions) with a mean age of 31 years. Sixty-two patients had pancreatic injury grade I-II and 9 had grade III-IV. Thirty-eight percent had Glasgow coma scale (GCS) <9 and 73% had injury severity score (ISS) >16. The level of pancreatic enzymes was significantly proportional to the grade of injury. Over half of patients required laparotomy, of them 12 patients had an intervention on the pancreas. Eight patients developed complications related to pancreatic injuries ranging from pancreatitis to pancreatico-cutaneous fistula while 35% developed hemorrhagic shock. Mortality was 31% and regardless of the grade of injury, the mortality was associated with high ISS, low GCS and presence of hemorrhagic shock. Conclusion: Pancreatic injuries following blunt trauma are rare and the injured subjects are usually young male. However, most injuries are of low-grade severity. This study shows that, regardless of the pancreatic injury grade, on-admission shock; higher ISS and lower GCS are associated with worse in-hospital outcomes. Non-operative management may suffice in patients with lower grade injuries, which may not be the case in patients with higher grade injuries unless carefully selected.